Disease Stage and Source of Infection in Newly Diagnosed HCV Related Cirrhotic Patients in Tertiary Care Hospital - RASHID IQBAL TALAT NAHEED, KHALID MAHMUD KHAN (Journal of Fatima Jinnah Medical University, 2018)
To note disease stage (Compensated, Decompensated) and source of infection in newly diagnosed Hepatitis C virus (HCV) related cirrhosis patients. Design: Cross sectional observational study. Place and duration of study: The study was carried out at Tertiary care hospital (Sir Ganga Ram Hospital Lahore) between Jan 2008 to Dec 2011 Patients and methods: Anti HCV antibody positive patients diagnosed cirrhotic patients who had come to know about first time ever diagnosed cirrhosis were included. Cirrhosis was diagnosed on clinical and ultrasonographic basis. Liver Biopsy was also used for the same purpose wherever possible or where consent was available. Each patient underwent detailed clinical history, laboratory, imaging, and endoscopic evaluation wherever required to note disease stage, main complaints and source of infection. Data was recorded on a prescribed Performa and analyzed as per aims and objectives of the study using SPSS. Results: Among 208 patients, 87% patients presented with decompensated cirrhosis. Abdominal distension (53.36 %), GI bleed with abdominal distension (16.82%), Haemetemesis / Melaena without any evidence of ascites (7.21 %), and Portosystemic encephalopathy was noted for (19.23% ) patients and hepatoma was found in (2.40%), were commonest presenting complaints. Major possible source acquiring HCV infection included; exposé to non disposable razors and blade by barbers and beauticians in 66 patients (31.73%), history of use of multiple / unsafe injections in 45 patients (21.63%), surgical and dental procedures in 42 patients (20.19%) and H/O blood transfusion were in 32 patients (15.38%), Anti HCV +ve spouse in 8 patients (3.84%) and no cause was found in 15 patients (7.21%). Conclusion: Most of newly diagnosed HCV related cirrhotic have decompensated disease .Hematemesis/Melaena and abdominal distension been major presenting complains, while exposure to non disposable razors and blades or barber are most frequent source of infection in these patients.